2011
DOI: 10.1111/j.1475-2743.2011.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic effects on the physical and chemical properties of subtropical coastal urban soils

Abstract: We investigated the effects of various anthropogenic factors on urban soil properties in subtropical, coastal Tampa, FL, USA. Specifically, we explored the influence of (i) urbanization as measured by land use, land cover, population density and years since urban development and (ii) socioeconomic conditions as reflected in household income and property values on bulk density (BD) and several key soil chemical properties. Results indicate that Tampa’s urban soils were affected to varying degrees by these facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
(156 reference statements)
1
17
1
Order By: Relevance
“…We also found significantly higher calcium concentrations in urban soils relative to remnant soils that included forests, pasture, shrub scrub, and wetlands. Our results were similar to those of the study of Hagan et al (2012) who reported no significant difference in soil calcium among commercial and residential sites, but we found significantly increased soil calcium in urban open areas (parks) relative to single-family homes, which we attributed to gypsum application by city municipalities. Soil concentration of sodium in Tampa (9-29 mg kg −1 ) (Hagan et al, 2012) was extremely low relative to the soils in Texas (20-1,142 mg kg −1 ); this can probably be attributed to differences in source water used for potable water.…”
Section: Soil Chemical Constituentssupporting
confidence: 94%
See 3 more Smart Citations
“…We also found significantly higher calcium concentrations in urban soils relative to remnant soils that included forests, pasture, shrub scrub, and wetlands. Our results were similar to those of the study of Hagan et al (2012) who reported no significant difference in soil calcium among commercial and residential sites, but we found significantly increased soil calcium in urban open areas (parks) relative to single-family homes, which we attributed to gypsum application by city municipalities. Soil concentration of sodium in Tampa (9-29 mg kg −1 ) (Hagan et al, 2012) was extremely low relative to the soils in Texas (20-1,142 mg kg −1 ); this can probably be attributed to differences in source water used for potable water.…”
Section: Soil Chemical Constituentssupporting
confidence: 94%
“…Municipal drinking water in Tampa has sodium concentrations of 55 mg L −1 (City of Tampa Water Quality Report 2012) compared with 226 mg L −1 in Bryan and College Station (Table 1). Whereas Hagan et al (2012) reported significantly higher soil sodium in residential soil, their soil sodium was not significantly higher compared with that in forest soil. Based on the vicinity of Tampa to the ocean, we believe that this may have been an effect of the forest canopy scavenging of oceanic aerosols in their study.…”
Section: Soil Chemical Constituentscontrasting
confidence: 64%
See 2 more Smart Citations
“…This also suggests that urban park soils have abundant earthworm populations regardless of age and vegetation and that they do not develop podzols typical to the boreal biome. Furthermore, as shown in several studies, urban soils typically have high pH (e.g., Craul and Klein, 1980;Jim, 1993;Hagan et al, 2012;Kuoppamäki et al, 2014), resulting from materials used in urban infrastructure that are high in calcium, such as concrete (Pouyat et al, 2007b). It is possible that substantial Ca inputs result in oversaturation of Ca and other cations in urban soils, which-in turn-inhibit clear soil stratification indicative of boreal forests.…”
Section: Vegetation Effects On the Vertical Stratification Of Soil Pamentioning
confidence: 99%